Comparative food web structure of larval macrolepidoptera and their parasitoids on two riparian tree species - Barbosa, P; Caldas, A; Godfray, C (2007)
Single species or groups of species can be subjected to differing levels of parasitism on different plants. Previous studies have reported that parasitism of larval macrolepidoptera in an assemblage on box elder (Acer negundo L.) was significantly greater than on black willow [Salix nigra (Marsh)]. In this study, quantitative food webs, parasitoid overlap diagrams and other food web attributes were used to identify and describe direct and indirect interactions, and to compare assemblages on each tree species. These comparisons helped identify possible mechanisms explaining the differential parasitism observed. Although links among numerically dominant species in each assemblage were not strong, links between numerically dominant and subdominant species were strong. That is, numerically dominant and subdominant species interacted via shared parasitoids. The degree of parasitoid sharing by numerically dominant and subdominant species differed in each tree. There was less sharing of parasitoids on black willow than on box elder. Further, on box elder, the majority of parasitoids affecting numerically subdominant species originated from numerically dominant species, unlike in willow. These results lead to a working hypothesis-the source/nursery hypothesis-that proposes that community-wide levels of parasitism are highest in circumstances in which numerically subdominant species share parasitoid species in common with numerically dominant species, and most parasitoids attacking subdominant species originate from numerically dominant species. Thus, differences in degree of sharing and the types of herbivores sharing parasitoids may explain differential parasitism. Further, the source/nursery hypothesis may explain why the vast majority of species in most assemblages are numerically subdominant. © 2007 The Ecological Society of Japan.